Preparation method of high-performance polyether-ether-ketone (PEEK) film

By preparing a high-performance SPEEK/SiO2 composite electrolyte film, the shortcomings of the existing SPEEK electrolyte film in terms of ionic conductivity are solved, and high ionic conductivity, water absorption and mechanical properties are improved, which significantly extends the service life of the fuel cell.

CN119823432AInactive Publication Date: 2025-04-15浙江明士达股份有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510102541.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing unmodified SPEEK electrolyte membranes are difficult to meet application requirements in terms of ionic conductivity.

Method used

High-performance SPEEK/SiO2 composite electrolyte film was prepared by vacuum drying, sulfonation reaction, ultrasonic assisted dispersion of SiO2, and supercritical CO2 extraction.

Benefits of technology

It improves the ionic conductivity, water absorption and mechanical properties of the film, reduces the methanol permeability, significantly extends the service life of the fuel cell, and improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823432A_ABST
    Figure CN119823432A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-performance polyether-ether-ketone (PEEK) film, and belongs to the technical field of electrolyte films, and the composite electrolyte film is prepared by adopting a supercritical carbon dioxide extraction process and taking sulfonated polyether-ether-ketone (SPEEK) as a basic raw material. The ionic conductivity of the film is improved, efficient transmission of charges in electrolyte is ensured, and the energy conversion efficiency of electrochemical devices such as a fuel cell is improved. The composite electrolyte film also has high water absorptivity, can effectively absorb and store moisture on the premise of maintaining the structural stability, has positive effects on maintaining the wet state of the electrolyte film and promoting proton conduction, can reduce the methanol permeability, and can improve the proton conduction efficiency by reducing methanol molecule permeation channels. Therefore, the service life of the fuel cell is remarkably prolonged, and the overall performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolyte membranes, and in particular to a method for preparing a high-performance polyetheretherketone (PEEK) membrane. Background Art

[0002] Polyetheretherketone (PEEK) is a semi-crystalline aromatic thermoplastic engineering plastic. Due to the rigid benzene ring, flexible aromatic ether group and polar aromatic ketone group that can improve the intermolecular force in the molecular chain, it has a regular structure and high crystallinity. Compared with other engineering plastics, it has excellent properties such as high temperature resistance, chemical corrosion resistance, radiation resistance, hydrolysis resistance, wear resistance, good mechanical properties, good flame retardancy, insulation, and easy processing. With the continuous development of polymer science and the improvement of membrane performance requirements for various applications, polyetheretherketone is very popular as a material with excellent performance and has been widely used in automotive parts, semiconductor manufacturing, aerospace, oil and gas, medical equipment, electronic appliances, food processing and other fields.

[0003] The abundant sulfonic acid groups introduced into sulfonated polyetheretherketone (SPEEK) make it have excellent ion transport properties, but the unmodified SPEEK electrolyte membrane still cannot meet the application requirements in terms of ion conductivity. In view of the above problems, the present invention proposes a method for preparing a high-performance polyetheretherketone (PEEK) film. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems in the prior art and to propose a method for preparing a high-performance polyetheretherketone (PEEK) film.

[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing a high-performance polyetheretherketone (PEEK) film, comprising:

[0006] S1. vacuum drying polyetheretherketone (PEEK) particles at 120°C for 12h;

[0007] Vacuum drying is used to remove moisture and other volatile impurities from PEEK particles to ensure the smooth progress of the subsequent sulfonation reaction, and vacuum drying can effectively prevent the oxidation and degradation of PEEK at high temperatures.

[0008] S2, dissolving the dried PEEK particles in concentrated sulfuric acid solution, and continuously stirring mechanically for 5 to 20 hours at 90°C to carry out sulfonation reaction;

[0009] The sulfonation reaction is to replace the hydrogen atoms in the PEEK molecular chain with sulfonic acid groups, thereby improving its hydrophilicity and ion exchange properties. Concentrated sulfuric acid, as a sulfonating agent, can effectively promote the reaction at 90°C. In addition, mechanical stirring can ensure that the sulfonation reaction proceeds evenly.

[0010] S3. After the reaction, the brown solution was placed in ice-cold deionized water for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was removed;

[0011] Rapid quenching can quickly lower the temperature of the reaction system, terminate the sulfonation reaction, and prevent excessive sulfonation. Using ice deionized water can quickly lower the temperature and precipitate SPEEK.

[0012] S4. Use deionized water to repeatedly rinse the SPEEK precipitate to remove sulfate and other impurities on the surface of SPEEK to ensure the purity of the product, and place it in a vacuum oven to dry for 1 day at a temperature of 60°C;

[0013] S5, weigh 5g of sulfonated sample (SPEEK), dissolve it in 200ml of NMP solution, weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h;

[0014] NMP as a solvent can dissolve SPEEK to form a uniform solution. The addition of SiO2 can enhance the mechanical properties and thermal stability of the composite film. Ultrasonic-assisted dispersion can ensure that SiO2 is uniformly dispersed in the NMP solution.

[0015] S6. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP and continue mechanical stirring for 24 h;

[0016] S7, subjecting the mixed solution to ultrasonic vibration for 120 minutes, casting it into a polytetrafluoroethylene mold to dry and shape, placing it in an oven at 90° C., drying it for 2 days to remove residual solvent;

[0017] Ultrasonic vibration can further ensure that the components in the solution are evenly distributed. Casting into a mold and drying and shaping can form a composite film with a specific shape. An oven temperature of 90° C. is used to accelerate the volatilization of the solvent and the drying of the composite film.

[0018] S8, placing the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction;

[0019] Supercritical extraction can remove residual NMP solvent and other volatile impurities in the composite membrane without damaging the structure and performance of the composite membrane.

[0020] S9. Slowly cool all samples to room temperature to obtain a transparent composite film.

[0021] Slow cooling can prevent the composite film from cracking and deforming during the cooling process.

[0022] Preferably, in step S2, the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution is 0.05 g / mL;

[0023] The concentrated sulfuric acid solution used was 98% analytical grade reagent.

[0024] Preferably, in step S2, the sulfonation time includes 5.0 h, 10.0 h, 15.0 h, and 20.0 h.

[0025] Preferably, in step S4, the SPEEK precipitate is rinsed with deionized water, and the pH is continuously monitored during the rinsing process until the water becomes neutral, indicating that the rinsing process is completed.

[0026] Preferably, in step S5, the NMP solution is N-methyl-2-pyrrolidone.

[0027] Preferably, in step S6, the mixed solution is continuously stirred using a magnetic stirrer to help the mixed raw materials completely dissolve in the solution.

[0028] Preferably, in step S8, the film is subjected to supercritical extraction using an Apeks supercritical extraction system;

[0029] Among them, the flow rate is 2mL / min, the temperature is 40°C, the pressure is 20MPa, and the time is 30min.

[0030] Preferably, in step S5, the ultrasonic treatment parameters include ultrasonic frequency of 20-40 kHz, ultrasonic power of 100-300 W, and ultrasonic time of 2 h.

[0031] Preferably, in step S3, the conductivity of the deionized water is required to be less than 15 μS / cm.

[0032] Compared with the prior art, the preparation method of the high-performance polyetheretherketone (PEEK) film has the following beneficial effects:

[0033] 1. The present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film, which uses a supercritical carbon dioxide extraction process and sulfonated polyetheretherketone (SPEEK) as a raw material to prepare a composite electrolyte film with high ionic conductivity, high water absorption and low methanol permeability.

[0034] 2. The present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film. Through a sulfonation reaction, sulfonic acid groups are introduced into the PEEK molecular chain, thereby enhancing the interaction between molecules, so that the film can withstand greater stress during stretching without being easily broken.

[0035] 3. The present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film, in which SiO2 nanoparticles are added to form a good interface bonding between the film and the SPEEK matrix, effectively dispersing stress, preventing crack expansion, and further improving the strength and toughness of the film.

[0036] 4. The present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film. After the sulfonation reaction, sulfonic acid groups are introduced into the PEEK molecular chain. These groups form effective proton conduction channels in the film, but also form a certain obstacle to the penetration of methanol molecules.

[0037] 5. The present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film, in which a physical barrier is formed in the film by adding SiO2 nanoparticles, thereby obstructing the permeation path of methanol molecules and further reducing the permeability of methanol, so that the film has excellent methanol barrier properties.

[0038] In summary, the present invention provides a method for preparing a high-performance polyetheretherketone (PEEK) film. By adopting a supercritical carbon dioxide extraction process and using sulfonated polyetheretherketone (SPEEK) as a basic raw material, a composite electrolyte film is prepared. The ionic conductivity of the film is improved, and the efficient transmission of charges in the electrolyte is ensured, which is beneficial to improving the energy conversion efficiency of electrochemical devices such as fuel cells. It also has high water absorption and can effectively absorb and store water while maintaining structural stability. It has a positive effect on maintaining the wet state of the electrolyte film and promoting proton conduction. In addition, the composite electrolyte film can reduce the methanol permeability and significantly extend the service life of the fuel cell and improve the overall performance by reducing the channels for methanol molecules to penetrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the DS and IEC bar graph in the specific embodiment 2 and embodiment 3.

[0040] Figure 2 This is a diagram of the methanol permeability test in specific embodiment seven. DETAILED DESCRIPTION

[0041] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments. Specific embodiment one:

[0043] A method for preparing a high-performance polyetheretherketone (PEEK) film, comprising:

[0044] S1. vacuum drying polyetheretherketone (PEEK) particles at 120°C for 12h;

[0045] Vacuum drying is used to remove moisture and other volatile impurities from PEEK particles to ensure the smooth progress of the subsequent sulfonation reaction, and vacuum drying can effectively prevent the oxidation and degradation of PEEK at high temperatures.

[0046] S2, dissolving the dried PEEK particles in concentrated sulfuric acid solution, and continuously stirring mechanically for 5 to 20 hours at 90°C to carry out sulfonation reaction;

[0047] The sulfonation reaction is to replace the hydrogen atoms in the PEEK molecular chain with sulfonic acid groups, thereby improving its hydrophilicity and ion exchange properties. Concentrated sulfuric acid, as a sulfonating agent, can effectively promote the reaction at 90°C. In addition, mechanical stirring can ensure that the sulfonation reaction proceeds evenly.

[0048] S3. After the reaction, the brown solution was placed in ice-cold deionized water for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was removed;

[0049] Rapid quenching can quickly reduce the temperature of the reaction system, terminate the sulfonation reaction, and prevent excessive sulfonation. Using ice deionized water can quickly reduce the temperature and precipitate SPEEK.

[0050] S4. Use deionized water to repeatedly rinse the SPEEK precipitate to remove sulfate and other impurities on the surface of SPEEK to ensure the purity of the product, and place it in a vacuum oven to dry for 1 day at a temperature of 60°C;

[0051] S5, weigh 5g of sulfonated sample (SPEEK), dissolve it in 200ml of NMP solution, weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h;

[0052] NMP as a solvent can dissolve SPEEK to form a uniform solution. The addition of SiO2 can enhance the mechanical properties and thermal stability of the composite film. Ultrasonic-assisted dispersion can ensure that SiO2 is uniformly dispersed in the NMP solution.

[0053] S6. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP and continue mechanical stirring for 24 h;

[0054] S7, subjecting the mixed solution to ultrasonic vibration for 120 minutes, casting it into a polytetrafluoroethylene mold to dry and shape, placing it in an oven at 90° C., drying it for 2 days to remove residual solvent;

[0055] Ultrasonic vibration can further ensure that the components in the solution are evenly distributed. Casting into a mold and drying and shaping can form a composite film with a specific shape. An oven temperature of 90° C. is used to accelerate the volatilization of the solvent and the drying of the composite film.

[0056] S8, placing the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction;

[0057] Supercritical extraction can remove residual NMP solvent and other volatile impurities in the composite membrane without damaging the structure and performance of the composite membrane.

[0058] S9. Slowly cool all samples to room temperature to obtain a transparent composite film.

[0059] Slow cooling can prevent the composite film from cracking and deforming during the cooling process.

[0060] Preferably, in step S2, the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution is 0.05 g / mL;

[0061] The concentrated sulfuric acid solution used was 98% analytical grade reagent.

[0062] Wherein, in step S2, the sulfonation time includes 5.0h, 10.0h, 15.0h, and 20.0h.

[0063] Wherein, in step S4, the SPEEK precipitate is rinsed with deionized water, and the pH is continuously monitored during the rinsing process until the water becomes neutral, indicating that the rinsing process is completed.

[0064] Wherein, in step S5, the NMP solution is N-methyl-2-pyrrolidone.

[0065] Wherein, in step S6, the mixed solution is continuously stirred using a magnetic stirrer to help the mixed raw materials completely dissolve in the solution.

[0066] Wherein, in step S8, supercritical extraction is performed on the film using an Apeks supercritical extraction system;

[0067] Among them, the flow rate is 2mL / min, the temperature is 40°C, the pressure is 20MPa, and the time is 30min.

[0068] Wherein, in step S5, the ultrasonic treatment parameters include ultrasonic frequency of 20-40kHz; ultrasonic power of 100-300w, and ultrasonic time of 2h.

[0069] Wherein, in step S3, the conductivity of the deionized water is required to be less than 15 μS / cm.

[0070] Among them, the SPEEK / SiO2 samples obtained by extraction were defined as SPEEK / SiO2-05, SPEEK / SiO2-10, SPEEK / SiO2-15 and SPEEK / SiO2-20 according to the initial sulfonation time of 5.0h, 10.0h, 15.0h and 20.0h, respectively. In addition, the unsulfonated samples were marked as PEEK / SiO2. Specific embodiment 2:

[0072] A SPEEK / SiO2 electrolyte film sample was prepared according to the steps in Specific Example 1, and the ion exchange capacity (IEC) of the SPEEK composite electrolyte membrane was analyzed by titration. The IEC value reflects the number and activity of ion exchange groups in the membrane and is an important parameter for measuring the proton conductivity of the membrane. In a fuel cell, the IEC value of a proton exchange membrane directly affects its proton conductivity and battery efficiency. Generally speaking, the higher the IEC value, the better the proton conductivity of the membrane, which helps to improve the efficiency of equipment such as fuel cells. Analyzing the ion exchange capacity (IEC) of a SPEEK composite electrolyte membrane by titration plays an important role in evaluating membrane performance, optimizing membrane preparation processes, and predicting membrane application performance. The specific contents of Example 2 are as follows:

[0073] 1. Preparation of composite membrane

[0074] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0075] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0076] 2. Ion exchange capacity (IEC) test

[0077] The SPEEK / SiO2 film was placed in a 1.0 mol / L NaCl solution and soaked for 48 hours to fully exchange with sodium ions. The exchanged solution was then collected and titrated with a 0.05 mol / L NaOH solution to obtain ICE, which was calculated as follows:

[0078] ICE = (V NaOH ×C NaOH ) / W0

[0079] Where: V NaOH is the volume of NaOH solution, L; C NaOH is the concentration of NaOH solution, mol / L; W0 is the dry mass of SPEEK / SiO2 film, g. Specific embodiment three:

[0081] According to the steps in the specific embodiment 1, a SPEEK / SiO2 electrolyte film sample is prepared, and the sulfonation degree of the SPEEK composite electrolyte membrane is determined. The sulfonation degree is the content of sulfonic acid groups in sulfonated polyetheretherketone (SPEEK), which directly reflects the structural characteristics of the electrolyte membrane. By measuring the sulfonation degree, the distribution and number of sulfonic acid groups in the electrolyte membrane can be understood, and then the formation and distribution of its ion channels can be inferred. As a proton donor and acceptor, the sulfonic acid group can form a continuous proton conduction channel in the membrane, thereby improving the proton conduction performance. The sulfonation degree will also affect the mechanical properties and stability of the electrolyte membrane. Too high a sulfonation degree will cause the membrane to swell excessively, reducing its mechanical strength and dimensional stability, while too low a sulfonation degree will affect its proton conduction performance. Therefore, by measuring the sulfonation degree, the preparation process of the electrolyte membrane can be optimized to obtain an electrolyte membrane with excellent mechanical properties and stability. The specific contents of Example 3 are as follows:

[0082] 1. Preparation of composite membrane

[0083] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0084] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0085] 2. Sulfonation degree (DS) test

[0086] The DS calculation formula is as follows:

[0087] DS=M w,p ICE / (1-M w,f ICE)

[0088] Where: M w,p is the molecular weight of the repeating unit of the non-functional functional group, g / mol; M w,f is the molecular weight of the repeating unit of the functionalized functional group (—SO3Na), g / mol.

[0089] 3. Results

[0090] The data obtained in Example 2 and Example 3 were statistically analyzed, and the results are summarized as follows: Figure 1 To further quantify the DS and IEC of the SPEEK / SiO2 electrolyte film, the solution after ion exchange was titrated. Figure 1IEC and DS of SPEEK / SiO2 with different sulfonation times. As shown in the figure, with the increase of sulfonation time, the IEC value of SPEEK / SiO2 film increases to 1.67mol / g, and the DS increases to 48%. When the sulfonation time exceeds 15h, the growth rate of IEC and DS of SPEEK / SiO2 film slows down, indicating that the sulfonation reaction tends to be saturated. Specific embodiment four:

[0092] According to the steps in the specific embodiment 1, a SPEEK / SiO2 electrolyte film sample is prepared, and the water absorption of the SPEEK composite electrolyte membrane is measured. The water absorption directly reflects the electrolyte membrane's ability to absorb and retain water. For a proton exchange membrane, maintaining a certain amount of water is the key to maintaining its proton conductivity. The water absorption can be used to evaluate the water retention capacity of the electrolyte membrane, and then predict its performance in applications such as fuel cells. In addition, the water absorption is closely related to the proton conductivity of the electrolyte membrane. An increase in the water absorption will increase the water molecule content in the membrane, which is beneficial to the conduction of protons. However, too high a water absorption may also lead to excessive swelling of the membrane and a decrease in mechanical properties. By measuring the water absorption, the preparation process of the electrolyte membrane can be optimized to obtain an electrolyte membrane with suitable proton conductivity.

[0093] The specific contents of the fourth embodiment are as follows:

[0094] 1. Preparation of composite membrane

[0095] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0096] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0097] 2. Water absorption test

[0098] The water absorption rate is the percentage of the mass difference between the wet and dry SPEEK / SiO2 films in the dry state. 2 The completely dried composite membrane sample was weighed (W0), then immersed in deionized water for 2 days to allow it to fully absorb water, and wiped dry with filter paper to obtain the wet membrane weight (W1). The water absorption rate (A%) is calculated as follows:

[0099] A=(W1-W0) / W0×100% Specific embodiment five:

[0101] Prepare a SPEEK / SiO2 electrolyte film sample according to the steps in the specific embodiment 1, and measure the AC impedance of the SPEEK composite electrolyte membrane. The AC impedance can directly reflect the ion conduction performance of the electrolyte membrane. By measuring the impedance of the electrolyte membrane under the AC electric field, the formation and distribution of its ion conduction channels, as well as the migration rate and efficiency of ions in the membrane can be understood, which is of great significance for evaluating the performance of the electrolyte membrane in applications such as fuel cells. In addition, the AC impedance data can also reveal the internal structural characteristics of the electrolyte membrane. By measuring the impedance spectrum at different frequencies, the distribution and size of components such as resistance and capacitance inside the electrolyte membrane can be analyzed, and then the uniformity and density of its internal structure can be inferred. Under long-term operation or different environmental conditions, the performance of the electrolyte membrane may change. By measuring the changes in AC impedance, the stability performance of the electrolyte membrane under these conditions can be understood, thereby providing an evaluation basis for its reliability and durability in practical applications. The specific contents of Example 5 are as follows:

[0102] 1. Preparation of composite membrane

[0103] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0104] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0105] 2. AC impedance detection

[0106] The ionic conductivity of SPEEK / SiO2 film was analyzed using an electrochemical workstation. The scanning range of the AC impedance spectrum was 100Hz to 100kHz, and the excitation signal was 10mV. The calculation formula of AC ionic conductivity (σ) is as follows:

[0107] σ = L / (R b ×A)

[0108] Where: L is the thickness of the SPEEK / SiO2 film, cm; A is the area of ​​the SPEEK / SiO2 film, cm 2 ; R b is the resistance of SPEEK / SiO2 film, Ω.

[0109] 3. Results

[0110] The data obtained from Example 4 and Example 5 were statistically analyzed, and the summary results are shown in Table 1. Table 1 shows the effect of sulfonation time on DS, water absorption, and ionic conductivity. As can be seen from Table 1, with the increase of sulfonation time, DS increased from 34.13% to 48.39%, and the corresponding water absorption increased from 20.54% to 28.65%. The reason for the above phenomenon is that the sodium sulfonate functional group is added to the SPEEK main chain, thereby improving the hydrophilicity of the SPEEK / SiO2 film. At the same time, the conductivity of the SPEEK / SiO2 film also increased from 1.54×10 -10 S / cm increased to 1.23×10 -4 S / cm. The interconnected water channels and sodium sulfonate functional groups in SPEEK / SiO2 provide a fast path for ion transport, allowing ions to migrate quickly in the matrix, thereby effectively improving the conductivity and ion exchange capacity of the material. In addition, the presence of SiO2 particles increases the interface in the matrix, which is more conducive to the conduction of water channels and ion transport.

[0111] Table 1 Effect of sulfonation time on water absorption and ionic conductivity of composite film samples Specific embodiment six:

[0113] According to the steps in the specific embodiment 1, a SPEEK / SiO2 electrolyte film sample is prepared, and the mechanical properties of the SPEEK composite electrolyte membrane are measured. Mechanical properties are an important indicator for evaluating the structural integrity of the electrolyte membrane. The electrolyte membrane needs to withstand certain pressure and stress in applications such as fuel cells. If the mechanical properties are insufficient, it may cause the membrane to rupture or deform, thereby affecting its ion conductivity and stability. By measuring the mechanical properties, it can be ensured that the electrolyte membrane has sufficient strength and toughness to maintain its structural integrity. Under long-term operation or harsh environmental conditions, the electrolyte membrane may be affected by factors such as wear, corrosion or aging, resulting in a decrease in its mechanical properties. Mechanical properties can reflect the durability of the electrolyte membrane under these conditions, thereby providing an evaluation basis for its reliability and life in practical applications. Mechanical properties also affect the dimensional stability, chemical stability and compatibility with other materials of the electrolyte membrane. By improving the mechanical properties, the comprehensive performance of the electrolyte membrane can be further enhanced so that it can better meet the needs of practical applications. The specific contents of Example 6 are as follows:

[0114] 1. Preparation of composite membrane

[0115] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0116] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0117] 2. Mechanical properties test

[0118] The mechanical strength and elongation properties were measured by a tensile stress-strain test system (Instron) at room temperature.

[0119] 3. Results

[0120] The mechanical strength and elongation properties were measured using a room temperature tension-strain test system (INSTRN), and the results are shown in Table 2. In the early stage of sulfonation (1-5h), due to the introduction of sulfonic acid groups, the interaction between PEEK segments may be enhanced, resulting in an increase in the tensile strength of the membrane. This enhancement may be due to the interaction between the sulfonic acid groups and the SiO2 particles, as well as the increase in segment rigidity caused by the sulfonic acid groups. As the sulfonation time is further extended, the tensile strength gradually increases, and the introduction of sulfonic acid groups and the dispersion of SiO2 particles gradually reach a relatively balanced state, resulting in a better tensile strength of the membrane. When the sulfonation time is 20h, the tensile strength of the composite membrane reaches its peak. As the sulfonation time gradually increases, the growth rate of the tensile strength gradually decreases.

[0121] Table 2 Mechanical properties of composite film samples at different sulfonation times Specific embodiment seven:

[0123] Prepare a SPEEK / SiO2 electrolyte film sample according to the steps in the specific embodiment one, and measure the methanol permeability of the SPEEK composite electrolyte membrane. In applications such as direct methanol fuel cells (DMFC), the electrolyte membrane needs to effectively prevent methanol from penetrating from the anode to the cathode to avoid voltage drop and performance loss. By measuring the methanol permeability, the barrier effect of the electrolyte membrane on methanol molecules can be understood, and then its applicability in related applications can be evaluated. In addition, methanol permeability directly affects the performance and stability of the fuel cell. When the methanol permeability is too high, it will cause the cathode catalyst to be poisoned and reduce the output voltage and power density of the battery. In addition, methanol penetration will also cause changes in the electrolyte concentration inside the battery, resulting in unstable battery performance. By measuring the methanol permeability, the preparation process and formula of the electrolyte membrane can be optimized to reduce the methanol permeability and improve the performance and stability of the fuel cell. The specific contents of Example 7 are as follows:

[0124] 1. Preparation of composite membrane

[0125] The polyetheretherketone (PEEK) particles were vacuum dried at 120°C for 12 hours, and the dried PEEK particles were dissolved in a concentrated sulfuric acid solution (98%, analytical grade) (the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution was 0.05 g / mL) at 90°C with continuous mechanical stirring for 5 to 20 hours (5.0 hours, 10.0 hours, 15.0 hours, and 20.0 hours) for sulfonation reaction. After the reaction, the brown solution was placed in ice deionized water (the conductivity of deionized water was <15 μS / cm) for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was fished out, and the SPEEK precipitate was repeatedly rinsed with deionized water until the water became neutral, and then dried in a vacuum oven for 1 day at 60°C.

[0126] Weigh 5g of sulfonated sample (SPEEK) and dissolve it in 200ml of NMP solution (N-methyl-2-pyrrolidone), weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP, and stir it mechanically for 24h continuously. Ultrasonic vibrate the mixed solution for 120min, cast it into a polytetrafluoroethylene mold to dry and shape, place it in an oven at 90℃, dry it for 2d, remove the residual solvent, and place the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction at a flow rate of 2mL / min, a temperature of 40℃, a pressure of 20MPa, and a time of 30min. Slowly cool all samples to room temperature to obtain a transparent composite membrane.

[0127] 2. Methanol permeability test

[0128] The methanol permeability of the SPEEK composite membrane was measured using a glass diffusion cell. The glass diffusion cell consisted of two compartments with a 3 cm diameter circular hole. 35 mL of methanol solution (methanol concentration was 3 mol / L) was added to one compartment, and 35 mL of deionized water was added to the other compartment. The solution in each cell was stirred continuously to keep it uniform. The methanol concentration in each cell was measured by gas chromatography (the measurement was carried out in a 30 °C water bath, and the membrane area was controlled at 5.3 cm 2 ).

[0129] 3. Results

[0130] Figure 2 is the methanol diffusion coefficient of the SPEEK / SiO2 film. Methanol permeability data is crucial to improving the efficiency of DMFC. If the methanol permeability is too high, methanol will penetrate from the anode to the cathode and react directly with oxygen to generate heat instead of electricity, thereby reducing the efficiency of the fuel cell. By reducing the methanol permeability of the film, this unnecessary reaction can be reduced, thereby improving the efficiency and energy density of the fuel cell. As can be seen from the figure, as DS increases from 34.13% to 48.39%, the methanol diffusion coefficient increases from 7.23×10 -7 cm 2 / s decreased to 2.11×10 -7 cm 2 The increase of DS leads to the increase of polarity of SPEEK / SiO2 film, thus reducing the diffusion coefficient of methanol.

[0131] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for preparing a high-performance polyetheretherketone (PEEK) film, characterized in that: include: S1. vacuum drying polyetheretherketone (PEEK) particles at 120°C for 12h; S2, dissolving the dried PEEK particles in concentrated sulfuric acid solution, and continuously stirring mechanically for 5 to 20 hours at 90°C to carry out sulfonation reaction; S3. After the reaction, the brown solution was placed in ice-cold deionized water for rapid quenching, and the white sulfonated polyetheretherketone (SPEEK) precipitate at the bottom was removed; S4. Rinse the SPEEK precipitate repeatedly with deionized water and dry it in a vacuum oven at 60°C for 1 day; S5, weigh 5g of sulfonated sample (SPEEK), dissolve it in 200ml of NMP solution, weigh 5g of SiO2 and dissolve it in another 200ml of NMP solution, and disperse it with ultrasonic assistance for 2h; S6. Mix the completely dissolved SPEEK / NMP solution with SiO2 / NMP and continue mechanical stirring for 24 h; S7, subjecting the mixed solution to ultrasonic vibration for 120 minutes, casting it into a polytetrafluoroethylene mold to dry and shape, placing it in an oven at 90° C., drying it for 2 days to remove residual solvent; S8, placing the completely dried SPEEK / SiO2 composite membrane in a supercritical CO2 solvent for supercritical extraction; S9. Slowly cool all samples to room temperature to obtain a transparent composite film.

2. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S2, the concentration of the polyetheretherketone particles in the concentrated sulfuric acid solution is 0.05 g / mL; The concentrated sulfuric acid solution used was 98% analytical grade reagent.

3. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S2, the sulfonation time includes 5.0 h, 10.0 h, 15.0 h, and 20.0 h.

4. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S4, the SPEEK precipitate is rinsed with deionized water, and the pH is continuously monitored during the rinsing process until the water becomes neutral.

5. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S5, the NMP solution is N-methyl-2-pyrrolidone.

6. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S6, the mixed solution is continuously stirred using a magnetic stirrer to help the mixed raw materials completely dissolve in the solution.

7. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S8, supercritical extraction is performed on the film using an Apeks supercritical extraction system; Among them, the flow rate is 2mL / min, the temperature is 40°C, the pressure is 20MPa, and the time is 30min.

8. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S5, the ultrasonic treatment parameters include ultrasonic frequency of 20-40 kHz, ultrasonic power of 100-300 W, and ultrasonic time of 2 h.

9. The method for preparing a high-performance polyetheretherketone (PEEK) film according to claim 1, characterized in that: In step S3, the conductivity of the deionized water is less than 15 μS / cm.

Citation Information

Patent Citations

  • Method for preparing homogeneously sulfonated poly (ether ether ketone) membranes by the casting method using organic solvents

    CN101407591A

  • Proton exchange membrane used for direct methanol fuel cell and preparation method thereof

    CN101562251A

  • Preparation method of composite proton exchange membrane for all vanadium redox flow battery

    CN102945972A

  • Sulfonated poly[(penta-sulfanilic acid)phosphonitrilic-polyetherether ketone] proton exchange membrane material and preparation method thereof

    CN103342875A

  • Surface sulfonated polyether ether ketone micro nanoparticle / sulfonated polyether ether ketone composite membrane, and preparation method thereof

    CN106750436A